Adherence to safety barriers in medication administration: patients' perception - Juliana Machado Campos Fleck; Rosana Aparecida Pereira; Ana Elisa Bauer de Camargo Silva; Fernanda Raphael Escobar Gimenes
Objective: to analyze the perception of patients about health professionals' adherence to safety barriers in medication administration. Method: cross-sectional and correlational study carried out in a hospital in the countryside of São Paulo, with a total of 249 adult patients admitted to the medical clinic. An electronic form developed by the researcher was used. Quantitative variables were analyzed in mean, median and standard deviation. Likert-type variables were calculated according to the perception score and the Bayesian Information criterion was used. The cutoff point for positive assessment of the patients' perception was 0.75. Results: the average perception score was 0.29 and, of the 15 barriers analyzed, eight are never adhered by professionals, in the opinion of most patients. Also, age was the only variable with statistical significance. Conclusion: the younger the patient, the better their perception of health professionals' adherence to safety barriers in medication administration.